Role of XRCC1 DNA Repair Gene Polymorphisms (Arg399Gln and Arg194Trp) on Outcome of Platinum Based Chemotherapy for Non-Small Cell Lung Cancer in North Indian Population - Naik, Poonam (My University, 2014)
The objective of this study was to detect the potential association of genetic variants in XRCC1 gene with lung cancer risk and survival analysis in North indian population. In total 201 lung cancer patients and 199 cancer-free controls enrolled for XRCC1Arg399Gln polymorphism study and 219 lung cancer patients and 204 cancer free patients enrolled for XRCC1Arg194Trp polymorphism in this study. The two polymorphisms of the gene XRCC1, Arg399Gln and Arg194Trp did not account as a risk factor for lung cancer and even not found to be protective also.No significant association was found for any of the three types of histology with genotype.There was no significant association of Arg399Gln and Arg194Trp genotypes in smokers.In case of XRCC1 Arg399Gln and Arg194Trp polymorphism, the heterozygous genotype showed a maximum median survival time and hence indicating a good survival response.When a combined survival analysis was carried out for both the polymorphic sites (Arg399Gln and Arg194Trp) the individuals carrying homozygous wild genotype showed maximum median survival time indicating good prognosis.
MS, DBTS
Keywords: lung cancer polymorphism